Diverse role of gut microbiota on reduction of ascites and intestinal injury in malignant ascites effusion rats treated with Euphorbia kansui stir-fried with vinegar. (1st March 2021) - Guo, Sijia; Jiang, Dongjing; Zhang, Qiao; Zhang, Yi; Yao, Weifeng; Cao, Yudan; Bao, Beihua; Tang, Yuping; Kang, An; Zhang, Li
Abstract: Ethnopharmacological relevance: Euphorbia kansui (EK) is the dried root of Euphorbia kansui S.L.Liou ex S.B.Ho. Clinically, processing with vinegar is for reducing toxicity of EK, and EK stir-fried with vinegar (VEK) is used to treat ascites and edema. VEK has been confirmed to reduce ascites by accelerating the promotion of intestinal contents. Aim of the study: The study aimed to investigate whether gut microbiota could affect the expelling water retention effects and the intestinal oxidative damage of EK and VEK on malignant ascites effusion (MAE) rats. Materials and methods: Pseudo-germ-free (PGF) MAE rats or probiotic intervented MAE rats were treated with EK/VEK. Related indicators such as serum, ascites, urine, feces, gastrointestinal tissues were analyzed, and the structure of the gut microbiota were also studied. The relationship between gut microbiota and the expelling water retention effects of EK/VEK where then further investigated. Results: VEK reduce the volume of ascites by promoting urine and feces excretion, AQP8 protein and mRNA expression, when comparing with the MAE rats, also VEK could regulate the disordered gut microbiota in MAE rats. Mixed antibiotics could diminish VEK's expelling water retention effects in MAE rats, but increased oxidative damage in intestine. While existence of gut microbiota (especially probiotics) played an important role in the protection of intestines in VEK treated MAE rats. Conclusion: VEK had obvious pharmacological effect on MAE and could regulate gut microbiota, but gut microbiota was not a necessary condition for its pharmacological effects. The probiotics played a synergistic role with VEK in the effects of expelling water retention and intestinal protection. Graphical abstract: Image 1